2005
DOI: 10.1002/marc.200400565
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Interface Technique for Determination of Initial Polymerization Kinetics

Abstract: Summary: A new procedure for the investigation of initial kinetics in a slurry olefin polymerization with a Ziegler‐Natta catalyst has been developed. It is based on the accurate timing of short polymerizations that result from the immediate start of a reaction between a catalyst separated in an oil phase and the remaining components of the system upon their being mixed together. The polymer samples are suitable for 13C NMR analysis and the number of active sites could be calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Skoumal et al employed oil to separate catalytic system from the monomer‐saturated heptane solution, and demonstrated the high mass transfer resistance of monomer in oil. [ 52 ] Thus there are reasons to believe that the lower activity of gas phase prepolymerization we obtained in the presence of oil is attributed to the mass transfer resistance imposed by the mineral oil covering on the surface of the catalyst particle. As an additional argument, the activity in the main stage polymerization (see Figure 15 and the following text) was higher for the entry with extra oil compared to the entry without extra oil, in accordance with the active sites number reported here.…”
Section: Resultsmentioning
confidence: 99%
“…Skoumal et al employed oil to separate catalytic system from the monomer‐saturated heptane solution, and demonstrated the high mass transfer resistance of monomer in oil. [ 52 ] Thus there are reasons to believe that the lower activity of gas phase prepolymerization we obtained in the presence of oil is attributed to the mass transfer resistance imposed by the mineral oil covering on the surface of the catalyst particle. As an additional argument, the activity in the main stage polymerization (see Figure 15 and the following text) was higher for the entry with extra oil compared to the entry without extra oil, in accordance with the active sites number reported here.…”
Section: Resultsmentioning
confidence: 99%
“…found that in propylene polymerization with a preactivated supported ZN catalyst, the initiation was completed within a few seconds. Skoumal et al . also observed a quick initiation in propylene polymerization.…”
Section: Introductionmentioning
confidence: 88%
“…Among these problems, the formation or initiation of catalytic centers in the first few minutes of olefin polymerization is especially important, as it will profoundly influence the kinetics, particle morphology, and polymer chain structure of the whole polymerization process. Many researchers have reported the kinetics and particle morphology of ZN‐catalyzed olefin polymerization in the initial stage . In a recent work, Busico et al .…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive fundamental studies in this field over the past decades, there are still many unsolved problems concerning the polymerization mechanism and relationships between catalyst structure and polymerization behaviors. The kinetics and mechanism of ethylene and propylene polymerizations with Z–N catalysts have been studied in a broad span of reaction durations ranging from less than 1 s to more than one hour [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. When ethylene and propylene polymerizations with the same catalyst are compared, several peculiarities in the reaction kinetics have been reported.…”
Section: Introductionmentioning
confidence: 99%